Variables of the family, school, and social environment context that determine bullying in adolescents in Medellín, Colombia, 2014 (2015)
This study determines the prevalence of bullying and the variables that explain the phenomenon in adolescents from educational institutions in Medellín. A survey involving school climate, family functionality and bullying was applied in a representative sample of 3,460 adolescents. The information was analyzed with descriptive measures, Z-test, prevalence ratios, Mann-Whitney test and logistic regression. The overall prevalence of bullying was 18.3%, being higher among those who report family dysfunction, delinquent behavior at school, bad relationships with teachers and insecurity in the neighborhood. The bullying is a complex phenomenon that involves the social framework, relationships within the family and the teachers.